Hemobilia due to cystic artery pseudoaneurysm following cholecystectomy: diagnosis and management, a case report. - Rossini, Matteo; Bonati, Elena; Cozzani, Federico; Marcato, Carla; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2019)
Hemobilia is an unusal cause of upper gastrointestinal bleeding and may be the result of the formation of an hepatic vessel pseudoaneurysm. This is a rare occurence after laparoscopic or open cholecistectomy. The most importants factor for pathogenesis are direct or indirect iatrogenic injuries during intervention and hepatic trauma. Clinical presentation may also be late and includes more frequently upper gastrointestinal bleeding due to pseudoaneurysm rupture, abdominal pain and jaundice secondary to bile duct compression. Therapies includes trans arterial embolization of feeding artery and percutaneous ingjection of embolic devices into the aneurysm. Surgery must be reserved for cathether based therapy failure. We report a case of a 66 year old man, presenting a month after cholecystectomy, complaining abdominal pain in the upper right quadrant and hematemesis. An EGDS exam showed hemobilia and computed tomography (CT) revealed a cistic artery pseudoaneurysm (PSA) wich have been successfully treated with hyperselective arterial embolization. Although this is a rare complication the surgeon must be aware of related symptoms and signs in order to sospect pseudoaneurysm as prompt recognition and treatment are essential. Untreated haemobilia may determine an immediate threat to life leading to acute haemodynamic instability We describe both diagnostic features and therapeutic strategies in comparison to the most recent literature. (www.actabiomedica.it)